The Implementation Of The Problem-Based Learning (Pbl) Model To Improve Mathematics Learning Outcomes Of Fifth-Grade Students At Uptd Sd Negeri 312, Wajo Regency - Musfirah, Musfirah; Zaid Zainal; Syamsidar (International Journal of Education, Vocational and Social Science, 2025)
The objective of this study is to determine the improvement and process of students' learning outcomes through the implementation of the Problem-Based Learning (PBL) model on the topic of area of plane figures. A qualitative approach was employed using the Classroom Action Research (CAR) method. The research involved one classroom teacher and 16 fifth-grade students—9 boys and 7 girls—during the 2024/2025 academic year at UPTD SD Negeri 312, Wajo Regency. Data collection techniques included observation, testing, and documentation. The research was carried out in two cycles, each consisting of two meetings that covered planning, implementation, observation, and reflection. Observation results of the teacher and students' learning processes in both cycles showed a good category. The number of students who successfully completed the test increased from 10 in Cycle I to 13 in Cycle II. It can be concluded that the implementation of the Problem-Based Learning (PBL) model in mathematics lessons can improve both the learning process and learning outcomes of fifth-grade students at UPTD SD Negeri 312 Cinnong Tabi, Wajo Regency.